2020
DOI: 10.3389/fpls.2020.00507
|View full text |Cite
|
Sign up to set email alerts
|

Macroclimate and Topography Interact to Influence the Abundance of Divaricate Plants in New Zealand

Abstract: Lusk et al. Climate, Topography and Divaricate Plants species richness and cover on sites where climatic restrictions on growth coincide with relatively high nutrient availability. The contemporary distribution of the divaricate form across New Zealand landscapes thus appears to be reasonably well explained by the hypothesized interaction of climate and fertility-mediated browsing, although experiments may provide more conclusive tests of this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Therefore, temperature is the most important factor that affects the yield and metabolic activities of the plants' community [49,50]. Moreover, there are interactions between topographical and climatic factors that influence the distribution of plants [51]. Our results showed that J. seravschanica had the lowest distribution in high slope and southern aspects.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, temperature is the most important factor that affects the yield and metabolic activities of the plants' community [49,50]. Moreover, there are interactions between topographical and climatic factors that influence the distribution of plants [51]. Our results showed that J. seravschanica had the lowest distribution in high slope and southern aspects.…”
Section: Discussionmentioning
confidence: 69%
“…Although our hypothesis involves soil fertility, our experiment did not test the effect of soil nutrients as it has previously been shown that divaricates are most prominent on fertile soils (Clarkson & Clarkson, 1994;Lusk et al, 2020a). Our experiment therefore TA B L E 6 Mortality (%) of broadleaved and divaricate seedlings apparently due to browsing, on unfenced plots in six New Zealand forests.…”
Section: Discussionmentioning
confidence: 98%
“…As well as reconciling the two competing explanations of the divaricate habit in New Zealand, this study therefore adds to evidence that climate modulates the adaptive value of structural defences against browsing, worldwide. The especially high incidence of spinescence in fertile savannas (Scholes, 1990 ), and of cage architectures on alluvial soils in New Zealand (Lusk et al ., 2020 ), suggest that a selection for structural defences is strongest when high nutrient availability coincides with strong climatic constraints on plant growth rates (Lusk et al ., 2016 ).…”
Section: Discussionmentioning
confidence: 99%